1999
DOI: 10.1093/rheumatology/38.10.997
|View full text |Cite
|
Sign up to set email alerts
|

Effect of methotrexate on blood purine and pyrimidine levels in patients with rheumatoid arthritis

Abstract: MTX decreases circulating purine and pyrimidine concentrations, and their availability for DNA and RNA synthesis, which may affect immune cell proliferation and protein (cytokine) expression. The absence of adenosine concentration changes and lack of ZTP formation is evidence against an AICAR/adenosine mechanism, although localized adenosine concentration changes cannot be excluded.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
41
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(42 citation statements)
references
References 20 publications
0
41
1
Order By: Relevance
“…Moreover, it has been also reported that uric acid has not been a strong antioxidant and might not protect against free radicals (Smolenska et al 1999). In the present study, there was no significant difference between the BD and the control groups in the levels of albumin, bilirubin and uric acid.…”
Section: Discussioncontrasting
confidence: 58%
“…Moreover, it has been also reported that uric acid has not been a strong antioxidant and might not protect against free radicals (Smolenska et al 1999). In the present study, there was no significant difference between the BD and the control groups in the levels of albumin, bilirubin and uric acid.…”
Section: Discussioncontrasting
confidence: 58%
“…In the work by Smolenska et al (1999), a single dose of methotrexate significantly reduced purine synthesis for a day without any concomitant increase in erythrocyte AICAR concentration. The observation that purine synthesis is inhibited for a day after a dose of methotrexate is consistent with and probably accounts for the methotrexate-mediated reduction in antigen-induced proliferation of T cells, although the clinical importance of reduced cellular proliferation 1 day a week is unknown.…”
Section: Methotrexate Increases Extracellular Adenosine Concentratmentioning
confidence: 97%
“…Other evidence against the hypothesis that methotrexate promotes adenosine release and adenosine mediates the anti-inflammatory effects were provided by two recent clinical studies (Egan et al, 1999;Smolenska et al, 1999). In the work by Smolenska et al (1999), a single dose of methotrexate significantly reduced purine synthesis for a day without any concomitant increase in erythrocyte AICAR concentration.…”
Section: Methotrexate Increases Extracellular Adenosine Concentratmentioning
confidence: 99%
“…33 In patients with RA, MTX is thought to act through inhibition of T cell proliferation. 35 We therefore hypothesized that genetic susceptibility markers may also be important predictors of MTX outcome. We report that the RA susceptibility allele of the SNP marker rs6920220 (OLIG3/TNFAIP3) was associated with being less likely to maintain MTX monotherapy by year 1 and year 2, in both IP and RA (Table 2).…”
Section: Discussionmentioning
confidence: 99%